Efficient electrochemical synthesis of 2H-MoS2/S-Doped graphene oxide composites for Binder-Free High-Performance supercapacitor electrodes - Hacinecipoglu, Ayse, V; Gencten, Metin (ELSEVIER, 2025)
The objective of this research is to examine the synthesis and characterization of molybdenum disulfide (MoS2) and sulphur-doped graphene oxide (S-GO) composites as potential materials for advanced supercapacitors. The study reports the first use of 2H-MoS2@SG-based materials, synthesized via an electrochemical method at room temperature, as binder-free electrode materials in supercapacitors. The synthesis of 2H-MoS2 involved cyclic voltammetry (CV), while sulfur-doped graphene oxide (SGO) was synthesized using chronoamperometry (CA). The materials were comprehensively characterized using various techniques, including Raman spectroscopy, Xray photoelectron spectroscopy, and X-ray diffraction (XRD), to gain insights into their chemical structure. The surface morphology of the composites was examined using scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDX). Additionally, the capacitive behavior changes over numerous cycles were evaluated through cyclic voltammetry, electrochemical impedance spectroscopy, and cyclic charge/ discharge tests. The highest specific capacitance achieved was 532.8 mF cm-2 at 10 mA cm-2 (266.4F/g at 0.5 A g -1 current density) with the 2H-MoS2@SG electrode and 247.4 mF cm-2 at 10 mA cm-2 (190.31F/g at 0.5 A g -1 current density) with the SG10 electrode. These values were measured at charge-discharge current rates of 10 mAcm-2 in a 1.0 M H2SO4 electrolyte. Moreover, the capacitive behavior of this electrode was tested over 5000 cycles, showing a capacitance retention of more than 99.2 % at the end of the 5000 cycles. 2H-MoS2@SG electrodes shows a high coulombic efficiency of 100 % over 5000 cycles at 0.5 A g -1 .
Keywords: Energy Storage Systems; Supercapacitor; Two-Dimensional Materials; Heteroatom Doped Graphene; Molybdenum Disulfide; OXYGEN FUNCTIONAL-GROUPS; DOPED GRAPHENE; ENERGY-STORAGE; ELECTROCATALYTIC ACTIVITY; MOLYBDENUM SULFIDE; MOS2 NANOSHEETS; HYBRID; NITROGEN; REDUCTION; Chemistry; Materials Science